Representations of Plains Indians along the Oregon Trail - Abbott, Patrick Kane (Kansas State University, 2009)
Monuments and memorials are how we record history on the landscape. History is created, preserved, and remembered by those who envision, design, and ultimately pay a visit to, these sites. The Oregon Trail is replete with interpretive sites relating to various events and people who lived along or traveled this route. From Independence, Missouri to Fort Laramie National Historic Site in Wyoming along the Great Plains section of the trail, Plains Indians are represented in thirty-two sites that convey various versions of history. The majority of these sites, twenty-seven, either ignore the Plains Indians or turn them into a stereotypical form of Sioux. These two representations give a sense that “No One is Home” or that “Siouxification” has occurred, a process by applying Sioux cultural traits to non-Sioux Plains Indians. The other five sites are categorized as “Getting It Right.” These sites either portray an accurate or close-to-accurate representation of the Indians and their role along the Oregon Trail. “No One is Home” is found all throughout the trail; “Siouxification” is clustered in the eastern study area; and “Getting It Right” primarily in the eastern portion.
Keywords: American Indians; Oregon Trail; Monuments; Memorials; Great Plains; Geography (0366); History, United States (0337)